1999
DOI: 10.1111/j.1600-0609.1999.tb01739.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of two mutations in platelet glycoprotein (GP) Ibα in two Finnish Bernard–Soulier syndrome families

Abstract: Bernard‐Soulier syndrome (BSS) is a rare hereditary bleeding disorder and macrothrombocytopenia which is caused by a defect in the platelet glycoprotein Ib/IX/V (GP Ib/IX/V) complex, the receptor for von Willebrand factor and thrombin. Here we report the molecular basis of the classical form of BSS in two unrelated Finnish patients, both with a life‐long history of severe bleeding. Flow cytometry and immunoblotting showed no expression of GP Ib/IX, GP Ibα, GP Ibβ or GP IX (less than 10%) in the patients' plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…The GPIba fragment was also not detected in the patient's plasma. To investigate whether different mutation types correlate with patterns of protein expression, we collected data from the previously reported patients harboring a homozygous GPIba mutation causing a premature stop codon (Table 2) [4,5,[9][10][11][12][13][14][15][16]. The GPIba protein expression profile in the present case was similar to that reported by Kanaji et al [12], who demonstrated a homozygous frameshift mutation in the GPIba gene, resulting in 294 amino acids followed by 40 altered amino acids.…”
Section: Discussionsupporting
confidence: 69%
“…The GPIba fragment was also not detected in the patient's plasma. To investigate whether different mutation types correlate with patterns of protein expression, we collected data from the previously reported patients harboring a homozygous GPIba mutation causing a premature stop codon (Table 2) [4,5,[9][10][11][12][13][14][15][16]. The GPIba protein expression profile in the present case was similar to that reported by Kanaji et al [12], who demonstrated a homozygous frameshift mutation in the GPIba gene, resulting in 294 amino acids followed by 40 altered amino acids.…”
Section: Discussionsupporting
confidence: 69%
“…This has led to a very limited gene pool (47). However, whereas a single mutation accounts for almost all cases in the majority of rare genetic diseases in Finland (48,49), for some reason there are least three different BSS founder mutations (36,38, the present report).…”
Section: Discussionmentioning
confidence: 70%
“…Most of the patients with BSS have mutations unique to their families, but the Asn45Ser, Cys73Ser and Phe55Ser point mutations in the GP IX gene (30)(31)(32)(34)(35)(36)(37), as well as the Leul29Pr0, Tyr505(TA 7') and a mononucleotide deletion at position 1932-1938 in the GP Iba gene (25,27,28,(38)(39)(40), have been reported more than once in unrelated families. As a part of a larger study (36,38), we had a unique opportunity to study five apparently unrelated families with BSS, in which the BSS phenotype was due to homozygous Asn45Ser substitution in the GP IX protein.…”
mentioning
confidence: 99%
“…Bernard–Soulier syndrome (BSS) and sitosterolaemia (Mediterranean stomatocytosis/macrothrombocytopenia) are classically described as recessive disorders, and heterozygous carriers of these disorders are usually asymptomatic or have mild bleeding symptoms . Supporting this, the cases studied here who were heterozygous for candidate defects in GPIBA , GPIBB and ABCG5 were either asymptomatic or had mild to moderate bleeding symptoms.…”
Section: Discussionmentioning
confidence: 99%